2007
DOI: 10.3727/000000007783991763
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Inducibility of the Human PDGF-A Gene Is Mediated by 5′-Distal DNA Motifs That Overlap With Basal Enhancer and Vitamin D Response Elements

Abstract: Retinoic acid (RA) upregulates expression of PDGF ligands and receptors in neonatal rat lung fibroblasts, a process likely to promote maturation of the lung alveolus and possibly microstructures of other organs. A mutational analysis of the gene encoding the PDGF-A ligand has identified a complex retinoic acid response element (RARE) located far upstream of the transcription start site, in a 5'-distal enhanceosome region previously shown to harbor basal and vitamin D-inducible enhancer activity. Maximal RA res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Retinoic acid, on the other hand, inhibits proliferation of embryonic palatal shelves in mice by downregulating Pdgfc activity (Han et al, 2006 ). Pedigo et al ( 2007 ) later reported the location of a complex retinoic acid response element in a region upstream of the transcription start site of PDGFA that was previously shown to harbor basal and vitamin D-inducible enhancer activity, which lends support to the connections seen between these entities in Figure 9 .…”
Section: Discussionmentioning
confidence: 70%
“…Retinoic acid, on the other hand, inhibits proliferation of embryonic palatal shelves in mice by downregulating Pdgfc activity (Han et al, 2006 ). Pedigo et al ( 2007 ) later reported the location of a complex retinoic acid response element in a region upstream of the transcription start site of PDGFA that was previously shown to harbor basal and vitamin D-inducible enhancer activity, which lends support to the connections seen between these entities in Figure 9 .…”
Section: Discussionmentioning
confidence: 70%
“…Of additional relevance is a complex enhanceosome located within the 5’-distal region of the PDGF-A gene (−7294 to −6787), which is highly activated in a number of transformed cell lines 15. This region contains a potent 66 bp enhancer (ACE66) which contains four tandemly arranged half-sites for binding of nuclear receptors, a ternary complex factor motif and overlapping response elements for vitamin D16 and retinoic acid 17. A high degree of transcriptional synergism is obtained with three directly repeated copies of the ACE66 element, ranging from 30-fold enhancement in HepG2 (hepatoma) and U2-OS (osteosarcoma) cells to 200-fold in JEG-3 and other choriocarcinoma lines.…”
Section: Introductionmentioning
confidence: 99%